2021
DOI: 10.1038/s41419-021-04349-5
|View full text |Cite
|
Sign up to set email alerts
|

RelA/MicroRNA-30a/NLRP3 signal axis is involved in rheumatoid arthritis via regulating NLRP3 inflammasome in macrophages

Abstract: NLRP3 inflammasome plays an important role in the pathogenesis of rheumatoid arthritis (RA). However, the post-transcriptional regulation of NLRP3 expression by miRNA in synovial macrophages is still not well understood. The aim of the study is to elucidate the mechanisms of RA with the focus on miRNAs mediated post-transcriptional regulation of the NLRP3 inflammasome. Here, we used NLRP3-deficient mice (NLRP3KO) to cross with TNFα-transgenic mice (TNFTG) to generate NLRP3KO/TNFTG mice, and compared their join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Subsequently, functional studies further proved that miR-30a directly interacts with the 3’ UTR of NLRP3 and mediates NLRP3 inhibition. 146 …”
Section: Deregulated Mirnas In Ramentioning
confidence: 99%
“…Subsequently, functional studies further proved that miR-30a directly interacts with the 3’ UTR of NLRP3 and mediates NLRP3 inhibition. 146 …”
Section: Deregulated Mirnas In Ramentioning
confidence: 99%
“…Finally, by constructing miRNA-hub gene regulatory network and TF-hub gene regulatory network, we found that hub genes, miRNAs and TFs might involved in CF and CF associated complications. USF2 [480], RELA [481], STAT1 [482], KLF5 [483] and TP53 [484] were closely related to arthritis. RELA [485] is believed to be related to the occurrence of pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NLRP3-mediated IL-1β secretion could be regulated by a variant within the gene locus encoding PTPN22, which has emerged as an important risk factor for auto-inflammatory disorders, including RA [ 171 ]. In addition to this, polymorphisms and expression of inflammasome genes are associated with susceptibility, disease activity and anti-TNF treatment response in RA [ 172 , 173 , 174 ], while it has also been described how several microRNA (miR-33, miR-20a and miR-30a) act as positive regulator of the NLRP3 inflammasome in RA macrophages [ 175 , 176 , 177 ]. More recently, the synergy of complement C1q with PTX3 in promoting NLRP3 inflammasome over-activation and pyroptosis in RA has been detailed [ 178 ].…”
Section: Interplay Between Mitochondrial Oxidative Stress Metabolic S...mentioning
confidence: 99%